Search 75,980 tutors
FIND TUTORS
Ask a question

Answers by Andrew R.

9t+6/t(t+3) = 7/(t+3) (9t+6)(t+3)=7t(t+3)      (Cross multiply the proportion) 9t+6=7t         (divide (t+3) from both sides) 2t+6=0              (subtract 7t from both sides) 2t=-6...

x6 - 9x4 - x2 + 9 = 0 = x4(x2-9) - (x2-9)  factor out x4 in the first two terms and a (-1) in the last two terms.                     = (x4-1)(x2-9)       collect like terms. Ex. a(x2-c)...

-4(2-3x)=7-2(x-3)     *first use the distributive property Ex. a(b+c)=ab+ac -8+12x=7-2x+6         *get all the terms with "x's" on each side. 12x+2x=7+6+8          *Collect like terms. Ex. 3x+5x=8x...